Does Board Gender Diversity Affect Accounting Conservatism and Financial Performance? - Sarwenda Biduri; Eny Maryanti; Essa Ries Ahmed; Nurasik (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2023)
The objective of this study was to determine the effect of Gender Diversity and Age Diversity on Accounting Conservatism. The control variable in this study is Gender Diversity and Age Diversity. The sampling method used was the purposive sampling technique. The number of companies used as the sample in this study was 13 companies. The data used were secondary data. The data analysis method used in this study was SEM-PLS. The results of this study showed that the Gender Diversity of the Board of Directors had a positive effect on Accounting Conservatism and financial performance. Gender Diversity of the Board of Commissioners had a positive effect on Accounting Conservatism and financial performance. Age Diversity of the Board of Directors had a positive effect on Accounting Conservatism And financial performance. Age Diversity of the Board of Commissioners had a positive effect on Accounting Conservatism And financial performance. Even though researchers have discussed gender stereotype change on its various outcomes or consequences, research is less. Hence, this study provides a synthesis of consequences and addresses the gaps in the area.